Educação superior em direito : entre a legalidade da norma e a subjetividade dos saberes - Braga, Mariza Alves (2006)
The dogmatical systematization of the Law as a Juridical Science has caused alteration in your original conception as a philosophy of joust and the social politcs relations. The superior Law education is centralized on the legatily of the norm in detriment of the subjectivety of necessary knowledge the formation of the bachelor. As the constructor of the necessary knowledge of the students, this formation must, through the critical and active pedagogy, rescue the sociological sense of the Law, promoting conditions to the bachelor to come near his relations with the political and philosophical knowledges that contribute to a juridical practices turned up to a social justice.